PELAKSANAAN PROGRAM NASIONAL PEMBERDAYAAN MASYARAKAT MANDIRI PERKOTAAN (PNPM-MP) EKONOMI BERGULIR KELOMPOK DI KELURAHAN SAIL KECAMATAN TENAYAN RAYA KOTA PEKANBARU TAHUN 2009-2013 - Ermita Rahayu; Raja Muhammad Amin (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
This study wants to investigate and analyze the implementation of the NationalProgram for Urban Community Empowerment (PNPM-MP) Revolving Economic Groupsin the Village District of Tenayan Raya,Sail Pekanbaru in 2009-2013 The background Thisstudy is not yet implemented effective government policy in tackling poverty through theNational Program for Community Empowerment Urban (PNPM-MP) Revolving EconomicGroup in the period 2009-2013 originating from the target inaccuracy of loan programsthat are not based on the goals and objectives of the program that prioritizes the poor andthe occurrence of non-payment of loan funds by the community of users and also agrowing perception in the community to be one because people assume that it is a loanassistance program grant from the government so that there is abuse of the loan funds.This study aims to find out what are the factors that affect the implementation ofthe PNPM-MP group in the Village Economic Revolving Sail Year 2009-2013 is based onthe theory of public policy and public policy implementation. This study used qualitativemethods are implemented in the Village Sail, the data obtained either directly or indirectly,which is then analyzed using descriptive data analysis techniques.Based on the research that has been done is used the Theory of Edward III Policy.Researchers concluded the implementation of the PNPM-MP group in the VillageRevolving Economic Sail in 2009-2013 is not going well as what to expect in theGuidelines for the implementation of the program. The factors that affect theimplementation of the National Program for Community Empowerment (PNPM-MP)Revolving Economic Group of the Year 2009-2013 is the communication factor is the lackof socialization programs to the community, the resource factors such as office facilitiesand equipment inadequate support in the implementation of the program,disposition ofimplementing which is not supported with an incentive or reward by implementingprograms that it is still not enough of course affect motivation program implementers.Keywords: Implementation,PNPM-MP Revolving Economic Groups